Online submission and analysis for final year project evaluation / Noridah Abu Bakar … [et al.] - Abu Bakar, Noridah; Abdul Hamid, Norlizah; Ismail, Sarimah; Kusrin, Jamiaton; Mohamed Kassim, Rezian-Na (Research Innovation Business Unit, 2014)
This project attempts to simplify the evaluation and consolidation process for Final Year Project Evaluation submission. The online form completed with all the rubric criterion will be listed together with associated Likert scale. The system will provide a database that allows the coordinator and lecturers to keep track of the students’ marks for final year project. The date of submission will be captured automatically and any duplication of marks will be detected by the system and prompted. The system also will allow the supervisor and coordinator to work online from anywhere. This encourages the use of technology in improving our productivity in work and supports the University’s campaign on blended learning. The current evaluation is done using either a hardcopy or softcopy in Microsoft Word template. This makes the consolidation by the program coordinator becomes tough when the submission is done either by hardcopy or through email as there are various aspects being evaluated as per listed in the rubrics. Furthermore, the dateline for submission always needs to be extended for marks entry into the RES system. This complicated process will not allow the coordinator to proceed with itemized analysis of the evaluation done by different supervisor. This planned system also will allow analysis of research topics conducted by the students under final year project. It will enable the tracing of same topic conducted by students, if any and at the same time will enable the faculty to control the issue of plagiarism and favouritism. Plagiarism can happen even though it can be traced using Turnitin software, as only a few of the lecturers have access to the Turnitin software. This system will enable the coordinator to identify and compare the marks given by list of supervisors in charge. This system also will enable the coordinator to identify the supervisor who has not yet entered the marks for their students, date of the evaluation submission and many more information that related to final year project evaluation submission. With that, the desired report can be produced and save for future use. Once the online evaluation is implemented, the process can be expedited and completed in a shorter time frame. It also supports the green computing where less paper is required.